Differential Effects of Calcium-Channel Blockers on Vascular Endothelial Function in Patients With Coronary Spastic Angina - Shimizu, Masatoshi; Miwa, Yoichi; Masai, Hiroyuki (Circulation Journal, 2009)
Background: The effects of the 3 classes of L-type calcium-channel blockers (CCBs) on vascular endothelial function have not been clarified in patients with coronary vasospasm. Methods and Results: Twenty-five normotensive patients (age 64.0±1.4 years) with coronary vasospasm were randomly treated for 3 months with benidipine, diltiazem, and verapamil, which belong to the dihydropyridine, benzothiazepine, and phenylalkylamine classes of CCBs, respectively. Endothelium-dependent flow-mediated dilatation (FMD), endothelium-independent nitroglycerin-induced dilatation in the brachial arteries, and plasma cyclic guanosine 3',5'-monophosphate (cGMP), a nitric-oxide-related product, were assessed before and after treatment. At baseline, the patients with vasospasm had significantly lower FMD as compared with normal subjects (n=8). Blood pressure did not differ among the 3 groups before and after treatment. Benidipine significantly increased FMD (from 4.7±0.6 to 7.4±1.1%, P<0.05) and plasma cGMP levels. In contrast, neither diltiazem nor verapamil affected FMD and cGMP levels. None of the treatments affected nitroglycerin-induced dilatation. Conclusions: Benidipine, but not diltiazem or verapamil, improves endothelial dysfunction beyond blood pressure lowering effects in patients with coronary vasospasm. Upregulation of the nitric oxide - cGMP system by benidipine may partly contribute to the improvement. The dihydropyridine class may be more beneficial for vascular endothelial function than the non-dihydropyridine classes of CCBs. (Circ J 2009; 73: 713 - 717)